The History of Pendennis - Thackeray, William Makepeace, 1811-1863 (Salt Lake City, UT : Project Gutenberg, 2005)
"The History of Pendennis" by William Makepeace Thackeray is a novel published between 1848-1850. Young Arthur Pendennis leaves his comfortable country home to make his way in London society. Through romantic misadventures, financial missteps, and encounters with rogues and social climbers, Pen navigates the treacherous waters of 19th-century English aristocratic life. Thackeray crafts a satirical bildungsroman featuring memorable characters like the snobbish Major Pendennis and the scheming flirt Blanche Amory, offering sharp insights into human character and the pursuit of fortune. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Pendennis
Release date is 2005-01-01
Tapio Riikonen and David Widger
Keywords: Humorous stories; Autobiographical fiction; Bildungsromans; Young men -- Fiction; Great Britain -- History -- Victoria, 1837-1901 -- Fiction